2000
DOI: 10.1095/biolreprod63.2.440
|View full text |Cite
|
Sign up to set email alerts
|

Testicular Recrudescence in the Male Black Bear (Ursus americanus): Changes in Testicular Luteinizing Hormone-, Follicle-Stimulating Hormone-, and Prolactin-Receptor Ribonucleic Acid Abundance and Dependency on Prolactin

Abstract: Testicular recrudescence in male black bears (Ursus americanus) is initiated in January and completed in May. The goals of this study in the black bear were to determine 1) if testicular abundance of LH-receptor (LHr), FSH-receptor (FSHr), and prolactin-receptor (PRLr) mRNA changes during recrudescence; 2) if these changes in mRNA abundance are associated with changes in serum LH, PRL, and testosterone (T) concentrations; and 3) if the spring increase in serum PRL concentrations is required for testicular recr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 29 publications
2
25
1
Order By: Relevance
“…Records in 2002 and 2005 from the Shou Shan Zoo in Kaohsiung showed that mating behavior was observed between June and September. An increase in photoperiod may cause luteinizing hormone receptor and prolactin receptor to increase, possibly related to an increase in the response between luteinizing hormone and the testes, which in turn stimulates the production of testosterone (Tsubota et al 1999;Komatsu et al 1997;Howell-Skalla et al 2000;Howell-Skalla et al 2002). Furthermore, the belief that breeding seasons are longer and earlier in subtropical zones has been verified by this study.…”
Section: Discussionsupporting
confidence: 69%
“…Records in 2002 and 2005 from the Shou Shan Zoo in Kaohsiung showed that mating behavior was observed between June and September. An increase in photoperiod may cause luteinizing hormone receptor and prolactin receptor to increase, possibly related to an increase in the response between luteinizing hormone and the testes, which in turn stimulates the production of testosterone (Tsubota et al 1999;Komatsu et al 1997;Howell-Skalla et al 2000;Howell-Skalla et al 2002). Furthermore, the belief that breeding seasons are longer and earlier in subtropical zones has been verified by this study.…”
Section: Discussionsupporting
confidence: 69%
“…Contrary to our hypothesis and previous studies in seasonal male species (black bear, Howell-Skalla et al 2000;bat, Hayashi et al 2002;sheep, Sanford et al 2002), expression of these isoforms did not differ between reproductively active and inactive stages in the female cat. Therefore, this observation suggested that Tr-FSHR did not have a regulatory function in seasonal FSH sensitivity in the latter species.…”
Section: Discussioncontrasting
confidence: 99%
“…Seasonally mediated variation in FSHR expression (mRNA or protein) has only been demonstrated in males of a few species (black bear, Howell-Skalla et al 2000;bat, Hayashi et al 2002; sheep, Sanford et al 2002) where reductions are directly correlated with spermatogenic declines. Therefore, this relationship is interesting to examine, especially given knowledge that a decrease in FSHR density has the potential of altering the response of rat granulosa cells to FSH from being stimulatory to antagonistic (Donadeu & Ascoli 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In all species studied, PRL acts by binding to a specific membrane receptor (PRL-R) (Clarke et al 1997;Jabbour et al 1998;Ohkubo et al 1998;Howell-Skalla et al 2000;Sandra et al 2000;Higashimoto et al 2001). Two main forms of PRL-R transcript have been identified (BoleFeysot et al 1998), one of which is specific for a short form of receptor (Boutin et al 1988), while the other is specific for a long form whose molecule possesses a cytoplasmic tail (Boutin et al 1988;Shirota et al 1990).…”
Section: Introductionmentioning
confidence: 99%